If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(v + -4) + -8v = -20 Reorder the terms: 4(-4 + v) + -8v = -20 (-4 * 4 + v * 4) + -8v = -20 (-16 + 4v) + -8v = -20 Combine like terms: 4v + -8v = -4v -16 + -4v = -20 Solving -16 + -4v = -20 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + -4v = -20 + 16 Combine like terms: -16 + 16 = 0 0 + -4v = -20 + 16 -4v = -20 + 16 Combine like terms: -20 + 16 = -4 -4v = -4 Divide each side by '-4'. v = 1 Simplifying v = 1
| 15286.9644=2*522.5274+l | | .50x+0.45(80)=0.25(98) | | -5.5x+0.67=-3.73 | | 14-5*n=3*n | | 13=2+x | | (7x-14)=(2x+5) | | x-x^2-7x+10=-3 | | 2y-12=y-20 | | -4=12+8x | | 26x*0.5=1000 | | x-x^2-7x+10=-13 | | 3+x=34 | | 2(2x+12)=2x+15+9 | | 26x*0.5=100 | | 3k-11-8k=-5-17k-3 | | 22=-6t-8 | | x*0.5=1000 | | -17(y-2)=17y+64 | | 8(c-17)=-24 | | 18=3+2(x+2) | | x*50=100 | | 2x+40=x+125 | | w=25h+40 | | 2(3-9x-6x)+5(4x+6)=6 | | 11x-32=67 | | M+22=118 | | 2(-4+7x)=30+6x-6 | | 2x^2-8=4x | | 3x^2-47=1 | | -3(n+7)=12 | | 4--2v=10 | | 28x^2-22x+4=0 |